(untitled) (Journal of Nepal Geological Society, 2004)
This paper deals with an application of New Australian Tunnelling Method (NATM) in low cover tunnelling in Lesser Himalaya of Nepal. The length of the tunnel is 365.8 m with a 8.2 m finished diameter. The average thickness of the rock overburden is 16- 18 m with a maximum of 30 m, whereas average side cover is 40 m. Top heading and multiple benching methods were applied for tunnelling work. The rational support design techniques were conceived together with Bieniawski’s Support Guideline for each standard support classes. Standard initial support system was designed according to NATM, to provide complete stabilization of excavation. It consisted of a combination of systematic rock bolts and shotcrete. The smooth blasting technique was adopted for the tunnel excavation. The specific charge was 1.39-1.47 kg/m3 A special emphasis was given in the collection of discontinuity data so that the rock mass could be evaluated effectively. Geomechanics classification for rock mass was used for the rock mass evaluation. The rock mass was also back evaluated by using Q and GSI classification on the basis of installed support. After the careful assessment of the data, the rock mass in the tunnel was classified into fair to poor according to RMR and Q and blocky / disturbed to very blocky / fair according to GSI. The rock mass parameters collected during the construction stage agree with the data collected at surface during feasibility and tendering stages. The rock mass classification based on the surface outcrop survey and drillings was a considerable success and found to be very close to the actual condition. The effectiveness of revised support system with steel rib was found to be negligible or minimum for tunnel support. Rock support deformation monitoring in the tunnel was regularly carried out to determine the efficiency and adequacy of the installed support.